Happenstance found eaudiobook - Catanese, P.W (Books of Umber, 2009)
Acclaimed author P. W. Catanese presents Happen-stance Found, the first in the rollicking Books of Umber fantasy series. Happenstance, a boy with unusual green eyes, awakens with no memories. Falling in with the adventurer Lord Umber and his band of misfits, this boy with many uncanny gifts soon discovers that he may be the strangest one of all. "Catanese packs a lot into the book: rich characterizations . well-chore-ographed action sequences and genuinely surprising twists at the end." -Publishers Weekly